Assessment of different antimicrobials to inhibit the growth of Zygosaccharomyces rouxii cocktail in concentrated apple juice. (October 2020) - Wang, Huxuan; Sun, Hongmin
Abstract: Zygosaccharomyces rouxii represents the main spoilage cause of concentrated apple juice, leading to waste of products or recalls. Essential oils components derived from plants have been found to present antimicrobial activities against various microbes. However, few work has been reported about their antimicrobial activities against Z. rouxii in concentrated apple juice. In this work, reparameterized Gompertz equation was used to evaluate the antimicrobial activities of different antimicrobials to inhibit the growth of a Z. rouxii cocktail (6.3 lg colony forming units/mL) composed of six strains isolated from concentrated apple juice and two strains from honey and grape must. The obtained mathematical models presented that thymol, carvacrol and trans-cinnamaldehyde were the promising options to inhibit Z. rouxii in 30 o Brix apple juice, reaching a maximal decrease on yeast growth of around 99.65 ± 0.61%. Whereas other antimicrobials showed lower antimicrobial activities with a maximal growth decrease of ranging from 67.13 ± 3.62% to 13.38 ± 1.16%. Additionally, the sensorial characteristics were not affected when the antimicrobials assayed were applied at the effective concentrations in commercial apple juice product. This work provided a theoretical feasibility that thymol, carvacrol and trans-cinnamaldehyde could be applied as natural preservatives for the control of Z. rouxii -related spoilage in fruit juice industry. Highlights: Plant essential oils components were assessed against Z. rouxii spoilage. Statistical modelling technique was applied for antimicrobial activity evaluation. Thymol, carvacrol and T-CNM were effective in inhibiting Z. rouxii cocktail. The components show potential "natural" replacements for traditional preservatives.